2015
DOI: 10.3109/0142159x.2015.1078890
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale multi-site OSCEs for national competency examination of medical doctors in Indonesia

Abstract: With 12 stations 15 min each, the reliability coefficient across station is intermediate. Content validity is good. It is feasible and acceptable to implement large-scale multi-site OSCEs in Indonesia. Examiners and examinees perceive good educational impact on OSCE implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In a large-scale multicenter study where 49 medical schools participated, Pearson's correlation coefficient between OSCEs and MCQs was 0.335 (P = 0.00) [15]. Sehlule et al…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a large-scale multicenter study where 49 medical schools participated, Pearson's correlation coefficient between OSCEs and MCQs was 0.335 (P = 0.00) [15]. Sehlule et al…”
Section: Discussionmentioning
confidence: 98%
“…In a large-scale multicenter study where 49 medical schools participated, Pearson's correlation coefficient between OSCEs and MCQs was 0.335 (P = 0.00) [15]. Sehlule et al [1] studied the correlation of different modes of assessment of medical students in hematology and integrated exam of paraclinical sciences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in previous studies, the implementation of an OSCE at the school or national level is challenging and requires many practical considerations [22,23], such as recruitment, training, and retention of personnel; test development and implementation costs; and facilities to administer the test [24]. Even though they are complex, costly, and resource intensive, many studies have reported that comprehensive OSCEs have numerous educational bene ts [23,[25][26][27]. For example, one study showed that over a 9-year period of administration, OSCEs produced important improvements in faculty teaching and student performance [25].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2013, Indonesia has conducted a national objective structured clinical examination (OSCE) for medical students as an exit exam, four times a year at each medical school . The national OSCE consists of 12 stations administered for six sessions over 3 days, and requires 72 different cases.…”
Section: What Problem Was Addressed?mentioning
confidence: 99%